2015
DOI: 10.2337/dc15-1447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on Adipose Tissue Glucose Metabolism in Different Depots in Patients With or Without Type 2 Diabetes

Abstract: OBJECTIVEWe investigated fat distribution and tissue-specific insulin-stimulated glucose uptake (GU) in seven fat compartments (visceral and subcutaneous) and skeletal muscle in morbidly obese patients with (T2D) and without (ND) type 2 diabetes before and 6 months after bariatric surgery. RESEARCH DESIGN AND METHODSA total of 23 obese patients (BMI 43.0 6 3.6 kg/m 2 ; 9 T2D and 14 ND) were recruited from a larger, randomized multicenter SLEEVEPASS study. MRI (for fat distribution) and [18 F]-fluorodeoxyglucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
1
40
0
1
Order By: Relevance
“…Although it is known that differences in the absolute expression of pro-inflammatory cytokines exist between visceral and subcutaneous adipose tissue in humans, gene expression patterns in both depots are equivalently associated with obesity [43, 57] and metabolic disease [43, 58, 59]. Related to this issue, Dadson et al [60] observed differences in insulin-stimulated glucose uptake between visceral and subcutaneous adipose tissue depots. However, the relative change in glucose uptake following bariatric/metabolic surgery was similar in both depots [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that differences in the absolute expression of pro-inflammatory cytokines exist between visceral and subcutaneous adipose tissue in humans, gene expression patterns in both depots are equivalently associated with obesity [43, 57] and metabolic disease [43, 58, 59]. Related to this issue, Dadson et al [60] observed differences in insulin-stimulated glucose uptake between visceral and subcutaneous adipose tissue depots. However, the relative change in glucose uptake following bariatric/metabolic surgery was similar in both depots [60].…”
Section: Discussionmentioning
confidence: 99%
“…Related to this issue, Dadson et al [60] observed differences in insulin-stimulated glucose uptake between visceral and subcutaneous adipose tissue depots. However, the relative change in glucose uptake following bariatric/metabolic surgery was similar in both depots [60]. Collectively, these findings suggest that assessments based solely on subcutaneous adipose tissue samples are not likely to grossly misrepresent the underlying processes associated with obesity-driven inflammation and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The participant recruitment process has been described previously . Briefly, morbidly obese participants were recruited from people undergoing bariatric surgery as part of their normal treatment at the Hospital District of Southwest Finland.…”
Section: Methodsmentioning
confidence: 99%
“…The participant recruitment process has been described previously. 20,21 Briefly, morbidly obese participants were recruited from people undergoing bariatric surgery as part of their normal treatment at the Hospital District of Southwest Finland. The surgical inclusion criteria were age 18-60 years and body mass index (BMI) ≥40 kg/m 2 (or ≥35 kg/m 2 with an additional obesity-related comorbidity).…”
Section: Participantsmentioning
confidence: 99%
“…The amount and distribution of adipose tissue (AT) are important contributing factors in the development of insulin resistance and type 2 diabetes . While hepatic and muscle insulin resistance are generally regarded as the key factors in disrupted glucose homeostasis in type 2 diabetes, AT glucose handling could also play an important role. AT has been shown to make a considerable contribution to insulin‐stimulated glucose uptake from the circulation .…”
Section: Introductionmentioning
confidence: 99%